Towards precision dosing of nanoparticles in mammalian cells - Singh, Hemang Raj (Nanyang Technological University, 2022)
Current in vitro assays of nanotoxicity studies rely on suspension-based delivery of ENMs into cells, which are in turn internalised by endocytosis. However, transformations of ENMs in suspension affect mass transport of particles from media to the cells, failure to characterise accurate dosages of NPs delivered into cells result in some of the disparity between in vitro and in vivo toxicity assays. This study explores alternative methods of intracellular delivery, relying on membrane-disruption, instead of endocytosis, to improve precision in delivery of ENMs into cells. Hydroporator is one such microfluidic intracellular delivery platform that hydrodynamically deforms cells, forming transient nanopores in plasma membrane through which particles can enter. Using carboxylic-functionalized polystyrene nanoparticles (COOH-PS NP) as model nanoparticulate system, our study found that while the hydroporator is able to achieve high-efficiency delivery (>94% of cells) of Polystyrene nanospheres into cells, it does put stresses onto the cells, inducing ROS generation and temporary cell-cycle stalling. However, it does not otherwise prompt COOH-PS, an otherwise non-toxic NP into toxicity. Further examinations also show that membrane-disruption based intake does not entirely prevent lysosomal capture but does allow more particles to evade such fate than in endocytosis-mediated uptake.